A New Control System of Point Light Source. (February 2019) - Yang, Faquan; Chen, Junbin; Cai, Zihong
Abstract: The spotlight source control system includes a single control mode spotlight source control system. A single controller controls 32 points through video signal to differential control to achieve single point control, and arbitrarily sets the white balance of a certain point through the menu; The main and auxiliary machine online mode spotlight source control system, the controller and controller are connected by DMX signals, which can realize 1000 controller cascades (that is, a total of 32, 000 points of cascade control can be realized), The system comes with a variety of effect modes, you can freely change the effect mode, connection mode and so on. The system has a wide range of applications in the landscaping of urban night scenes.